An Active Power Filter Method to Improve the Line Current Spectrum of PWM Locomotive Rectifiers with Load Unbalance - Kuppa, V.; Wolfs, Peter; Senini, S. (University of Tasmania, 2005)
Locomotives in heavy haul and high speed passenger operations represent several megawatts of electrical load. Single phase power collected by a pantograph is typically rectified by multiple PWM converters. The converter switching instants are phased to ensure ripple current cancellation, assuming that the converter loads are balanced. Partial failures may result in unbalanced operation with reduced cancellation. The resulting harmonics may adversely impact the signalling systems and/or result in over voltage effects due to resonance in the overhead supply system. This paper examines a 4MW locomotive with three rectifier modules and a device switching frequency of 900 Hz. This results in a 5400 Hz ripple frequency in the mains current. Ideal balanced operation of converters is compared to an unbalanced operation case. Unbalanced cases include rectifier failures, inverter failures and changes in the relative balance of power delivered to each axle of the locomotive. This paper will consider what may be the most frequently occurring case; that of loss of load in one traction motor due to wheel slip. Current ripple cancellation is partially lost in this case and lower frequency current components can be produced. An active filter is proposed as a means to retain an acceptable harmonic performance for the locomotive.